2014
DOI: 10.1016/j.egypro.2014.07.005
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Leaching Tests to Assess Metal Release from Contaminated Marine Sediment under CO2 Leakages from CCS

Abstract: This study provides a better knowledge of key parameters controlling the mobility of Dissolved Organic Carbon (DOC), As, Cd, Cr, Cu, Ni, Pb and Zn from contaminated marine sediment in contact with acidified seawater using static and dynamic standard leaching tests. These procedures have been modified in order to use different leaching agents, L/S ratios, contact times and pH values that simulate seawater acidification under CO 2 leakages scenarios. Studied sediment from a potential area of CO 2 storage, shows … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 18 publications
1
3
0
Order By: Relevance
“…V release was observed in all experimental conditions, according to previous studies reporting high V mobility at neutral/marine pH (Brunori et al, 2005; Reijonen et al, 2016). In contrast, As was not remobilized during our experiment conducted at neutral/marine pH, in agreement with previous studies showing low As solubilization from contaminated marine sediment and processing waste under aerobic and neutral pH conditions (Al-Abed et al, 2007; Martín-Torre et al, 2013). In the neutral/marine pH region, the low As release is probably due to the co-sorption of As and Fe in sediments (Saulnier and Mucci, 2000; Al-Abed et al, 2007).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…V release was observed in all experimental conditions, according to previous studies reporting high V mobility at neutral/marine pH (Brunori et al, 2005; Reijonen et al, 2016). In contrast, As was not remobilized during our experiment conducted at neutral/marine pH, in agreement with previous studies showing low As solubilization from contaminated marine sediment and processing waste under aerobic and neutral pH conditions (Al-Abed et al, 2007; Martín-Torre et al, 2013). In the neutral/marine pH region, the low As release is probably due to the co-sorption of As and Fe in sediments (Saulnier and Mucci, 2000; Al-Abed et al, 2007).…”
Section: Discussionsupporting
confidence: 93%
“…Acidic industrial effluent induced an increase in the content of several trace metals (e.g., Cd, V) in our resuspension experiment and could influence metal dynamics by modifying some physico-chemical parameters, especially pH, which control TE chemical form and mobility (Kiratli and Ergin, 1996; Eggleton and Thomas, 2004; Millero et al, 2009; Wang Z. et al, 2015). Martín-Torre et al (2013) have shown that metal response to pH variation varies from one element to another. According to our study, Cd was not controlled by neutral/marine pH (7–8.5) range, because it forms strong chloro complexes in seawater, which are weakly influenced by pH change (Millero et al, 2009; Martín-Torre et al, 2013; Bruland, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This acidification could mobilise elements from marine and estuarine sediments (Rodríguez- Romero et al, 2014;Zheng et al, 2012). The risk of potential contaminant release from sediment is usually assessed using leaching tests (Ho et al, 2012;Martín-Torre et al, 2014;Payán et al, 2012a). The mobility and availability of contaminants from a sediment matrix are highly dependent on the leaching pH (Coz et al, 2007), so pH dependence leaching tests are essential for analysing the importance of these parameters.…”
Section: Introductionmentioning
confidence: 99%